POLA KOMUNIKASI LEADER DAN AGEN ASURANSI PRUDENTIAL DI MASA KEBIASAAN BARU (NEW NORMAL) - Vania Putri Azaria (2023)
ABSTRACK This study aims to discuss the experience of communication patterns that occur between leaders and Prudential insurance agents during the new normal period by using the Coordinated Meaning Management Theory. The method used is descriptive phenomenology which is based on Edmund Husserl's philosophy. The sampling technique was carried out by purposive sampling, with the main data collection technique namely in-depth interviews. The results of this study the authors get several groups of themes from the experiences told by informants. To analyze communication patterns that occur between leaders and agents, a hierarchy of meaning from the Coordinated Meaning Management Theory is used which consists of communication content, speech acts, contracts or relationships, episodes, life scripts, and cultural patterns. Then explained their initial experience as an insurance agent. Then explained what are the activities as an insurance agent who takes shelter in an agency office. Next, they explain their work as insurance agents, selling, recruiting, educating and helping customers. After that, the interactions and communication patterns that occurred between leaders and agents were explained before the pandemic, during the pandemic, and the new normal. Keywords: Communication Patterns, Leaders, Insurance Agents, Phenomenology